The pathogenesis, therapeutic targets and drugs of polycystic ovary syndrome - Chen, Yawen; Sun, Xiaoxiang; Xia, Xuan; Chen, Kaiqi; Zeng, Fang (Frontiers in Endocrinology, 2026)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine and metabolic disorder characterized by a high incidence rate and multiple complications, posing significant threats to women’s health and quality of life. The etiology of PCOS involves a complex interplay of genetic, metabolic, hormonal, immunological and environmental factors, though its precise mechanisms remain incompletely understood. This review explores the roles of oxidative stress, autophagy, ferroptosis, epigenetic modifications, post-translational modifications, chronic low-grade inflammation, and gut microbiota in the pathogenesis of PCOS. Current therapeutic strategies often combine lifestyle modifications with pharmacological interventions to address the multifaceted symptoms of PCOS. Drawing on the latest research, this review highlights advanced glycation end products (AGEs), sex hormone-binding globulin (SHBG), and microRNAs (miRNAs) as promising targets for PCOS prevention and treatment. Future research should focus on developing targeted drugs for these molecular pathways, offering new avenues for managing PCOS. This review will provide a scientific foundation for advancing PCOS treatment strategies.